Establishing ethos and envisioning a new Africa: Kwame Nkrumah’s invention at the 1958 All-African People’s Conference (Journal for Studies in Humanities and Social Sciences, 2015)
In 1958, Kwame Nkrumah, the Prime Minister of Ghana, called for a conference of independent heads of state in Africa. It was a novelty in Africa. The conference was to provide a formal continental platform for the political deliberation of Africa by Africans. The paper carefully focuses on the nuances and purpose of Nkrumah’s invention. First, the work argues that Nkrumah strategically invented a rhetoric which sought to establish his ethos as a Pan Africanist whose leadership was crucial in the quest to free Africa from colonial domination. Secondly, the paper examines, through Nkrumah’s rhetoric, how the deliberative nature of the Accra conference was turned into an epideictic one. This paper has implication(s) for the role of rhetoric in the decolonisation of Africa.